PENERAPAN METODE PEMBELAJARAN GALLERY WALK UNTUK MENINGKATKAN AKTIVITAS DAN KETUNTASAN BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KOLOID KELAS XI IPA 3 SMAN 6 PEKANBARU - Wulandari, Riska; ', Rasmiwetti; ', Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aimed to find out the improvement of the student?s learning activity and completeness by using Gallery Walk learning method on colloid topic at XI IPA 3 grade of SMAN 6 Pekanbaru in academic year 2015/2016. This research is class action research with two cycles research design. The sample of this research was XI IPS 3 grade students. They were given a corrective action in learning process by using Gallery Walk learning method. The data were collected by giving test and observation method. The researcher analyzed the data descriptively by using percentage technique. Based on the result of the data analysis, it can be concluded that the use of Gallery Walk learning method can improve student?s learning activity and completeness in colloid topic at XI IPA 3 grade of SMAN 6 Pekanbaru. It can be seen by the improvement of student?s learning activity from 57,987% at the first cycle to 72,192% at the second cycle, and learning completeness from 78,78% at the first cycle to 87,87% at the second cycle.Keywords: Gallery Walk Learning Method, Learning Completeness, Learning Activities